No difference in endothelial microvasculation measured by peripheral arterial tonometry in patients with Sjögren’s disease and matched controls - Tapken, Franziska Maria; Zehrfeld, Nadine; Abelmann, Malin; Müller-Vahl, Anna Charlotte; Benz, Sabrina; Seeliger, Tabea; Skripuletz, Thomas; Witte, Torsten; Sonnenschein, Kristina; Bauersachs, Johann; Bavendiek, Udo; Thum, Thomas; et al. (Frontiers in Medicine, 2025)
Sjögren’s disease (SjD) is a connective tissue autoimmune disorder characterized by inflammatory infiltration of the exocrine glands, leading to symptoms such as dryness, pain, and fatigue. Additionally, up to 50% of patients may experience extraglandular manifestations. SjD patients face a higher cardiovascular risk, including severe events like myocardial infarction and strokes, partly due to an increased likelihood of subclinical atherosclerosis. Therefore, identifying SjD patients at an early stage is essential to reduce morbidity and mortality. In this study, SjD patients who met the current ACR/EULAR 2016 classification criteria were consecutively enrolled in our outpatient clinic. A control cohort was recruited through a multimedia call for participation. To assess changes in endothelial functions, a reactive hyperemia index (RHI) was calculated using peripheral arterial tonometry with the EndoPAT® measurement device. RHI values below 1.67 were considered pathological. The dataset consists of 49 SjD patients and 27 healthy controls. Both groups had similar ages and comparable cardiovascular risk factors. No differences in RHI were observed between the two cohorts. The only significant factor that was predictive for a low RHI was an increased body mass index (p = 0.036). These findings suggest that EndoPAT measurements may not be a suitable method for detecting changes in endothelial function specific to patients with SjD.